Clinico-therapeutic and diagnostic aspect of Dipyllidium caninum infection in a dog - V K, Varun; P S, Maurya; M V, Jithin; Singh, Ajit Kumar; Deepak, Desh; John, Jeny K; Ramakant; T K, Sarkar (Indian Journal of Veterinary Medicine, 2024)
A 2.5 month old Bhotia pup was presented to Department of Veterinary Clinical Complex, College of Veterinary and Animal Sciences, with the history of dullness, anorexia, loose faeces and melena since last 4 days. White cucumber seed shaped segments in faeces and scooting behaviour was also noticed. Faecal sample with proglottids were collected in a sterile vial and was sent to Department of Veterinary Parasitology for coproscopic examination. The proglottids were processed by standard protocol for the identification of the endoparasite. Proglottids were noticed in chain and single. The direct faecal sample examination revealed large number of typical egg capsules which were round in shape containing large number of eggs, characteristic of Diphyllidium caninum. Pup was treated with praziquental @ 5 mg/kg body weight orally and animal recovered completely.